The quality of mobile phone services provided by Romanian operators, from consumers' perspective - Doru Alexandru Pleșea; Roxana Sârbu; Zoltan Kato (Amfiteatru Economic Journal, 2013)
The mobile services are distinguished through their quality, either we speak about the way the client is approached and placed in the centre of the operator's actions, or about the services the client benefits in his capacity as a client. The Romanian mobile operators' services have greatly evolved from their launch in 1997. Along these times, the mobile operators brought more value to these services, due to their need to meet the consumers' expectations with services of high quality and competitiveness. Usually the Romanian consumers place the price in the forefront of their service/mobile phone services acquisition, but an objective analyze of the quality of the mobile phone services has to take into account both technical aspects of the services and the interfacing services too. Therefore, this paper takes into account technical characteristics of the services such as national telephony coverage, data transmission services coverage, the signal quality, maximum speed of data transfer as well as related services such as distribution network, sales and support sales services, after-sales services, and range of available terminals. Based on mobile services comprehensive analysis made available to consumers by the major players on the Romanian market, this paper aims to highlight the main reasons of the consumers' satisfaction and dissatisfaction.
Keywords: D18; L96; 330; mobile telephony services; the quality of services; customer satisfaction; the technical characteristics services; related services